2020
DOI: 10.18632/aging.103298
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical characteristics and outcomes of patients with coronavirus disease 2019 at different ages

Abstract: Background: Information about the clinical characteristics and mortality of patients with coronavirus disease 2019 at different ages is limited. Results: The older group had more patients with dyspnea and fewer patients with fever and muscle pain. Older patients had more underlying diseases, secondary infection, myocardial injury, renal dysfunction, coagulation dysfunction, and immune dysfunction on admission. More older patients received immunoglobulin therapy and mechanical ventilation. The proportions of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 36 publications
(46 reference statements)
6
69
2
8
Order By: Relevance
“…A previous study reported findings from 99 patients with COVID-19, and the results suggested that SARS-CoV-2 infection in humans was more likely to affect older men with comorbidities and may result in severe respiratory diseases [ 12 ]. Zhao et al also reported that older patients were more likely to develop critical illness with a significantly higher mortality rate [ 13 ]. Consistent with these studies, in this cohort, we observed a greater number of men than women, and the patients were older in the nonsurviving group than in the surviving group.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported findings from 99 patients with COVID-19, and the results suggested that SARS-CoV-2 infection in humans was more likely to affect older men with comorbidities and may result in severe respiratory diseases [ 12 ]. Zhao et al also reported that older patients were more likely to develop critical illness with a significantly higher mortality rate [ 13 ]. Consistent with these studies, in this cohort, we observed a greater number of men than women, and the patients were older in the nonsurviving group than in the surviving group.…”
Section: Discussionmentioning
confidence: 99%
“…379 studies were identified after screening titles and abstracts, and 12 studies with 10,304 cases were included conclusively after full-text review. 6 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Of those, 8 studies reported OR and 4 reported HR, and 8 studies reported the association between cerebrovascular disease and the fatal outcomes. Seven studies came from China, two from America, two from Korea, and one from UK.…”
Section: Resultsmentioning
confidence: 99%
“…Os estudos evidenciaram que a população idosa é mais susceptível à contaminação por COVID-19, bem como à evolução de quadros graves. Além disso, demonstrou-se um amplo espectro clínico da doença nesta população, na qual foi constatada sintomatologia mais agressiva, diversa e relacionada com situações de saúde pré-existentes à infecção 6,7,[9][10][11][12][13] . Observa-se que os idosos apresentam sintomas mais atípicos e com duração ligeiramente mais longa desde o início da sintomatologia até a sua admissão, tornando-se mais difícil a identificação da infecção por COVID-19 de forma precoce.…”
Section: Discussionunclassified
“…Como, por exemplo, o estado mental alterado, demonstrado pelo estudo de Ward 14 , que pode ser um dos primeiros sinais clínicos da infecção por COVID-19 e esse sinal deve ser considerado como um indicativo da doença, possibilitando o tratamento com antecedência, mesmo sem os sintomas respiratórios e febre 14 . Além disso, uma questão que pode explicar a ocorrência de quadros graves é o fato de haver uma propagação da infecção devido à não percepção desses sintomas atípicos, contribuindo para o seu mau prognóstico 11 .…”
Section: Discussionunclassified